Pemberdayaan Masyarakat Dalam Pengelolaan Homestay Berbasis Komunitas Lokal di Desa Wisata Nagari Sungai Pinang, Pesisir Selatan Sumatera Barat - Delmira Syafrini; Nurlizawati Nurlizawati; Lia Amelia (ABDI: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2022)
This paper aims to explain how to increase community knowledge for management homestay based local community in Sungai Pinang, West Sumatra. This problem interesting because Sungai Pinang is one of the villages that has great potential to become a mainstay tourism village for West Sumatra and one of the locations that is quite attractive to local and foreign tourists. However, the development of Nagari Sungai Pinang tourism has not been accompanied by the readiness of the community to become a tourism community. One of the indicators is the issue of participation in supporting important tourism infrastructure, such as lodging/ homestays. In Sungai Pinang there is currently only one inn, and even then it is managed by a private sector which is commercialized, so it does not have an impact on the economy of the local community. Whereas residents' houses are an important resource that can be used as homestays. This problem is the reason for the importance of fostering the Sungai Pinang community. As a solution to the problems encountered by the partners above, community-based homestay management training is carried out according to standards, by utilizing local residents' homes. The community needs to be given education about homestay management standards that pay attention to service and comfort to visitors, because lodging is one of the factors that can influence tourist interest, including the welfare of local communities. The form of activity provided is socialization and training in managing residents' houses to become homestays. The results of this activity indicate that there is an increase in the knowledge and ability of the community to managing homestays, including knowledge of homestay management that supports tourism development in Sungai Pinang.